Modern physics - Serway, Raymond A. (Thomson Brooks/Cole, 2005)
Provides an introduction to relativity, quantum mechanics, and statistical physics as well as applications of these theories to molecular physics, condensed matter physics, nuclear physics, particle physics, and cosmology.